1990
DOI: 10.1097/00000658-199012000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inhalation Injury in Burn Trauma A Canadian Experience

Abstract: From 1977 to 1987, 1705 thermally injured patients were admitted to the Firefighters' Burn Center at the University of Alberta Hospitals. Thirteen hundred forty-four were male (78.8%) and 361 were female (21.2%), with a mean total burn surface area (TBSA) of 15.1 (SEM +/- 0.4%) and a range of 1% to 99% TBSA. Sixteen hundred thirty-five patients survived to be discharged from hospital, with an overall survival rate of 95.9%. One hundred twenty-four burn patients (7.3%) suffered concomitant inhalation injury dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(50 citation statements)
references
References 20 publications
4
43
1
2
Order By: Relevance
“…Potential survivability for those children who were incinerated is obviously zero, and for those with more than 60 per cent of surface area burnt who also sustained some inhalational injury, survivability is estimated at less than 20 per cent. [10][11][12][13][14] Evidence of airway obstruction was present in 61 (81 per cent) of the 68 children for whom this factor was recorded at post mortem. Seven of the 82 children (8 per cent) survived their injuries for one d ay or more.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential survivability for those children who were incinerated is obviously zero, and for those with more than 60 per cent of surface area burnt who also sustained some inhalational injury, survivability is estimated at less than 20 per cent. [10][11][12][13][14] Evidence of airway obstruction was present in 61 (81 per cent) of the 68 children for whom this factor was recorded at post mortem. Seven of the 82 children (8 per cent) survived their injuries for one d ay or more.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this low figure is the life-threatening influence of tracheal and pulmonary burns sustained by an entrapped victim breathing hot gases. 4,11,12,24 Adult data have indicated that smoke inhaled by an entrapped victim results in 62 per cent mortality. 25 Intubation and airway control is the urgent resuscitation measure for all children who are rescued from house fires and from motor vehicle conflagrations.…”
Section: Discussionmentioning
confidence: 99%
“…When combined with cutaneous burns, inhalation injury increases fluid requirements for resuscitation, [1] the incidence of pulmonary complications, [2] and the mortality rate. [2][3][4] Inhalation injury is produced by either thermal or chemical irritation due to inspiration of smoke, burning embers, steam, or other irritant or cytotoxic materials in the form of fumes, mists, particulates, or gases. [3,5,6] The damage can be the result of direct cytotoxic effects of the aspirated materials or a consequence of the inflammatory response.…”
Section: Methodsmentioning
confidence: 99%
“…Among annual reported injuries in USA two million are ranked in burn category (US fact sheet 2000). The mortality in South Asia extended over 10/100,000 burn injuries (Tredget et al, 1990). In biggest city of Pakistan, Karachi the adult mortality rate due to burns was, 6.8/100,000 for men and 14.1/100,000 for women, respectively in the year of 2002 (World Health Organization ;.…”
Section: Mortality Rate Associated With Hospital Acquired Infectionsmentioning
confidence: 99%